Epidemiology and Causes of Postpartum Hemorrhage - M.Sallo, Andi Kamal; Irma, Irma; Darmansyah Arif, Safriadi (The SDGS Forum Communication, 2024)
Maternal mortality is an indicator that shows the welfare of women in a country is not guaranteed. The urgency of maternal and child health has been on the agenda of the Sustainable Development Goals. This means that maternal mortality must be immediately reduced to 70 per 100,000 live births. The purpose of this study was to examine the epidemiology and underlying causes of postpartum hemorrhage in women. The study was designed in the form of a cohort study using 14 female respondents who were patients at Mitra Manakarra Mamuju Hospital. The study was conducted in July–December 2023. The results found that factors of education, parity, history of anemia, and birth spacing are risk factors for bleeding. Causes of bleeding in postpartum respondents include placental retention, uterine atony, and birth canal tears. It is therefore important to prevent bleeding by treating anemia at birth, spacing births between 2 and 5 years, and increasing maternal knowledge.